Benefits, Limits, and Risks of GPT-4 as an AI Chatbot for Medicine - Lee, Peter; Bubeck, Sébastien; Petro, Joseph (New England Journal of Medicine, 2023)
The uses of artificial intelligence (AI) in medicine have been growing in many areas, including in the analysis of medical images, the detection of drug interactions, the identification of high-risk patients, and the coding of medical notes. Several such uses of AI are the topics of the “AI in Medicine” review article series that debuts in this issue of the Journal. Here we describe another type of AI, the medical AI chatbot.